Phosphorescent Flower Emitting Light in a Dark Room - Ward, Lock (Wonders of electricity and the elements, being a popular account of modern electrical and magnetic discoveries, magnetism and electric machines, the electric telegraph and the electric light, and the metal bases, salt, and acids, 1870)
Illustration depicting a flower temporarily illuminated through the use of phosphorescent powder.
Keywords: Scientific illustration; Science--Study and teaching; Chemical elements; Science--Experiments; Phosphors; Phosphorescence